UPAYA PENINGKATAN KUALITAS PELAYANAN MELALUI KOMUNITAS PELANGGAN SEBAGAI DIGITAL MARKETING TERHADAP KEPUASAN KONSUMEN PADA UMKM SASAYUR KABUPATEN SLEMAN - Siti Maratus Soleha; Nanang Kusuma Mawardi; Artita Devi Maharani (JURNAL ILMIAH AGRITAS, 2026)
This study aims to analyze the effect of service quality delivered through customer communities as a digital marketing strategy on consumer satisfaction at Sasayur MSMEs in Yogyakarta. The background of this research is based on the increasing use of digital technology and social media as marketing media, which enables MSMEs to build active and responsive customer communities that play a role in improving service quality. The study employs a mixed-method sequential explanatory approach, in which quantitative data are collected and analyzed in the first stage, followed by qualitative data to strengthen the findings. The research sample consists of 100 respondents who are members of the Sasayur customer community. Data analysis techniques include SEM-PLS to assess the relationships among variables, while the effectiveness of the community is measured using a percentage formula. The results indicate that service quality has a positive effect on consumer satisfaction, and customer communities as a digital marketing strategy also contribute to enhancing consumer interaction, convenience, and trust. Customer communities are proven to be effective as a medium for communication, information dissemination, and complaint resolution. Furthermore, the effectiveness analysis shows that the Sasayur customer community falls into the effective category, indicating its ability to support improvements in service quality and consumer satisfaction. This study implies that MSMEs need to optimize digital communities to maintain service consistency, build closer relationships with consumers, and increase customer loyalty. Keywords: service quality, customer community, digital marketing, consumer satisfaction, effectiveness.